The Students’ Challenges in Speaking for Debate - Yulianti, Dwi; Budiastuti, Riana Eka; Mulyadi, Dodi (Proceedings Series on Social Sciences & Humanities, 2025)
One of the most difficult and exciting forms of academic communication available to students is debate. One of the most challenging communication obstacles students face in their academic endeavors is debate speaking. This study aims to find and investigate the common issues debated by students. The study focuses on numerous important areas, including speaking anxiety, time management, framing arguments, handling counterarguments, improving debate forms, and team coordination inside a debate team. Data collecting and processing for this study used quantitative descriptive approaches. The debate class consists of forty college students registered. Five student interviews plus a prepared questionnaire helped to compile the data. The results show that most students struggle with controlling limited speaking time during debates, have trouble with spontaneous reasoning, and suffer from speaking anxiety. Two other noted major obstacles were inadequate team coordination and a lack of knowledge concerning discussion procedures. To improve students' speaking ability in debate environments, lecturers and debate coaches should offer specialized training programs stressing debate strategy, speaking fluency, and team collaboration techniques. This study clarifies students' speaking challenges and offers reasonable suggestions for strengthening debate education in universities.